Cognitive System of Students in Solving Proportion Problems - Nita Fatma Fauziah (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
Cognition and learning mathematics is two things that aren’t could separated. Cognitive is related to “thought” domains with how a student obtain process and use knowledge. Cognitive systems are implemented from the domain of memory, manipulate knowledge and use that knowledge. Besides this, system is tasked with processing information or knowledge effectively in completing tasks. This research purpose is to describe students’ cognitive system in solving proportion problem based on Marzano's taxonomy. This research is descriptive qualitative research using test about proportion and an interview guide to collect data. subject in this reseach are 2 students at SMPN 3 Sumenep. The results showed that the subject has do system cognitive that is retrieving knowledge, comprehending knowledge, analyzing knowledge, and using Knowledge even if one subject not yet perfect.